Pure motor demyelinating neuropathy: deterioration after steroid treatment and improvement with intravenous immunoglobulin. Issue 7 (July 1994) - Donaghy, M; Mills, K R; Boniface, S J; Simmons, J; Wright, I; Gregson, N; Jacobs, J
Abstract : Within one month of starting oral prednisolone treatment weakness unexpectedly increased in four patients aged 34 to 75 years with purely motor forms of acquired chronic demyelinating neuropathy. By contrast, steroids produced the expected improvement in 11 other patients with symmetric sensorimotor chronic inflammatory demyelinating polyneuropathy. Two of the patients with purely motor demyelinating neuropathy were subsequently treated with high dose IVIg (0.4 g/kg/day for five days) with prompt improvements in strength measurements and motor nerve conduction. Thus IVIg seems to be the treatment of choice and steroids should be used with extreme caution, if at all, in patients with purely motor forms of acquired demyelinating polyneuropathy.